The development of quality indicators for systemic lupus erythematosus using electronic health data: A modified RAND appropriateness method. Issue 3 (3rd May 2020) - Yajima, Nobuyuki; Tsujimoto, Yasushi; Fukuma, Shingo; Sada, Ken-ei; Shimizu, Sayaka; Niihata, Kakuya; Takahashi, Ryo; Asano, Yoshihide; Azuma, Teruhisa; Kameda, Hideto; Kuwana, Masataka; Kohsaka, Hitoshi; et al.
Abstract: Objective: Quality indicators (QIs) are tools that standardize evaluations in terms of the minimum acceptable quality of care, presumably contributing for the better management of patients with systemic lupus erythematosus (SLE). This study aimed to develop QIs for SLE using electronic health data. Methods: The modified RAND/UCLA Appropriateness Method was used to develop the QIs. First, a literature review was conducted. Second, the candidate QI items that were available to be evaluated using the electronic health data were extracted. Third, the appropriateness of the items was assessed via rating rounds and panelists' discussions. Results: We found 3621 articles in the initial search. Finally, 34 studies were reviewed, from which 17 potential indicators were extracted as candidate QIs. Twelve indicators were selected as the final QI set through the process of appropriateness. The median appropriateness of these 12 indicators was at least 7.5, and all of them were without disagreement. The QI included assessment of disease activity, treatment of SLE, drug toxicity monitoring, treatment of glucocorticoid complications, and assessment of SLE complications. Conclusion: We formulated 12 QIs for the assessment of patients with SLE based on electronic medical data. Our QI set would be a practical tool as a quality measure.